Un-strangering 'the stranger' in a strange land : a multi-perspective, participant-led, exploration of in/ex-clusion in NZ mainstream high schools - privileging the voices of senior 'high-functioning' autistic students : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Crooks, Sharon (Massey University, 2021)
New Zealand’s (NZ) ‘inclusive’ school policies enable autistic students to attend a mainstream school of their choice, with the expectation they will belong, feel accepted, contribute, and participate in ‘school life’. Research has typically focused on biogenetic origins and diagnostic specificity, providing medicalised and stereotypical ways of understanding autistic people. Few qualitative studies have explored autistic students’ understandings and everyday lived experiences of ‘being autistic’ and ‘being in an inclusive mainstream high school’. Excluding their voice from research, necessarily constrains development of policy, pedagogy, and praxis, which might facilitate more inclusive experiences for this population of students. This study was the first in NZ to focus on the lived experiences of autistic adolescents in their senior years (Levels 1-3 NCEA). A multi-perspective, qualitative phenomenological design enabled three tertiary students, three parents, and seven advocates, to augment contributions from five high-functioning autistic adolescents. This research was underpinned by a feminist standpoint epistemology and Bronfenbrenner’s bioecological model, privileging first person experiences and contextual influences. Interpretative Phenomenological Analysis enabled participants’ understandings and experiences to be explored. Tertiary students illumined how medical model understandings of disability constrained and enabled identity formation in high school and implicated being understood. Most of the autistic participants drew on neoliberal ‘governmentality’ to problematise barriers to inclusion, namely ‘governance’ (dominant culture, school rules, and regulation of ‘space’), teacher performativity, and curriculum management. Salient interpersonal barriers included authoritative teachers, social cliques, ‘invisible’ bullying, and ‘one-off’ grievances. ‘Being excluded’ was painful and resulted in feeling ‘de-valued’, impacting motivation and opportunities for success. Facilitators to inclusion were embedded within meaningful interactions, demonstrative care, and common interests, aiding a sense of acceptance, and belonging, but not always resulting in ‘contributing’ and ‘participating’. High school was experienced by autistic participants as a political site where in/ex-clusion ‘gets done’ through ordinary technologies that ‘sift and shift’ students, according to sameness and difference, or ontological ‘otherness’. This study addresses prominent diagnostic and identity issues, academic and social achievement, and support, all of which are primary concerns for educationalists (including educational psychologists) striving to understand inclusion and improve outcomes for autistic students.
Keywords: Autistic youth; Education (Secondary); Mainstreaming in education; Autistic youth; High school students; Attitudes; New Zealand; 520302 Clinical psychology